Dark Matter and Real-Particle Field Theory (Global Journal of Science Frontier Research, 2022)
Based on real-particle field theory, this research demonstrates that dark matter comprises elastic electrons with a full cosmic background. In the real-particle field theory, real particles are elastic particles with both mass and volume. Real particles have three independent motion modes and two symmetrical interactions. The evolution of the real-particle field follows a set of Poisson equations. The theory shows that the electric and magnetic potentials represent electronic interactions of mass attraction and motion repulsion. The electromagnetic and darkmatter fields are essentially elastic electron fields. The laws of mechanics, gravitation, and electromagnetism of classical physics can be inferred from the real-particle field theory. In the electron field, electronic clusters are photons with the energy proportional to vibration frequency. The mechanic features of photons can be characterized by their volume, mass, and elasticity. Furthermore, the radiation of electronic clusters follows Planck's law, which indicates that dark matter has a uniform density and no photonic current in the cosmic background. It is shown that matter essentially comprises discrete particles, and the matter field is merely a statistical convolution effect of a large number of particles. Consequently, dark matter particles contribute to the structural formation of all matter in the universe.
Keywords: dark matter; elastic particles; photons; interactions; unified field